PERANCANGAN SISTEM REMOTE IP TABLE DAN INSTRUSION DETECTION SYSTEM (IDS) DENGAN SNORT PADA JARINGAN LAN - Adhi Prakosa, Bayu; Hendrawan, A. Hendri; Apriana, Windi (Krea-TIF: Jurnal Teknik Informatika, 2015)
The design of Remote Iptablesand Intrusion Detection System (IDS)system with Snort has been done. LocalArea Network Model Network is widelyapplied to various customer segments.Problems of decreasing LAN networkperformance, due to a number of ping ofdeath attacks and SYN flooding attacksthat affect all computers connected on theLAN network. Based on that, we need aproper attack detection and preventionsystem to help the administrator in LANnetwork security. Remote Iptables andIntrusion Detection System with Snort,warning system of real-time attacks willbe sent via SMS, a number of syntax withiptables remote using SMS Gateway, andblocking in real time. Stages used for theachievement of research objectives, is theidentification of problems, design systemrequirements, system implementation andtesting. Detection results are 4 (four)types of information, ie attack time, typeof destination IP attack, and IP source.Detection and blocking of attacks basedon a number of syntax is done bycomparing the packet to the rules in theform of integration through SMSGateway for the ease of the administratorin the execution of blocking. Blockingattacks in the form of 3 (three) types ofinformation, the source IP, the type ofattack, and security policy. Based onthese results, some attacks can bedetected in real time against 4 types ofinformation, blocking attacks integratedvia SMS Gateway in the form of packetcomparisons to rules, and blockingattacks in the form of Remote Iptableswith 3 (three) types of information.Keywords: LAN Network, RemoteIptables, Intrusion Detecion System, SMSGateway.